China scholars and the media: improving an awkward, important relationship - Sullivan, Jonathan (Cambridge University Press, 2014)
Public interest in China, as reflected in the level of media attention, is burgeoning in the West and elsewhere in the world. This interest is driven by China's increasing presence and importance in the lives of people around the world; and for the same reason is likely to continue growing. Since media discourses are the main way in which Western publics receive information about China, contributing to media reports and helping journalists reach deeper understandings is an important task and opportunity for academics whose specialist knowledge of China is often more nuanced than that of generalist China correspondents. Although developments in the two professions are demanding closer and more frequent interactions, many scholars are reluctant to engage. This is partly due to structural disincentives within the academy, and partly due to obstacles in the scholar–media relationship. Focusing on the latter, the objective of this article is to illuminate how China scholars and journalists currently interact, and to identify means to increasing their efficiency and sustainability.